SUSTAINABILITY BANK PERKREDITAN RAKYAT DENGAN KINERJA SISTEM INFORMASI AKUNTANSI KEBERLANJUTAN - purnama, sri; Wasita, Putu Aristya Adi; Ardana, I Made Dwi Wira (Faculty of Economics and Business, Universitas Warmadewa, 2024)
This study aims to examine the development of a sustainability accounting information system based on contingency theory. In today's digital era, BPRs face many data sets, including financial and non-financial data. However, empirical evidence is still scarce on how sustainability issues are linked or integrated into the company's internal information system. The initial data used in this study came from 80 respondents from BPRs in Badung Regency. The results show that there is a significant relationship between stakeholder engagement, especially internal stakeholders, and sustainability accounting information systems; most of the surveyed BPRs include sustainability strategies as core BPR strategies; however, there is no relationship between sustainability accounting information systems and BPR strategies, and firm size does not moderate sustainability accounting information systems with BPR strategies. The limitation of this study relates to the small sample size, which only uses respondents from BPRs in Badung Regency. The results of this study are important to encourage the social responsibility of BPRs by developing a sustainability accounting information system.